EDUCATIONAL AUTONOMY AS AN IMPORTANT PREREQUISITE FOR THE FORMATION OF FUTURE PHDS' RESEARCH COMPETENCE IN THE CONDITIONS OF POSTGRADUATE STUDIES - Oliinyk Iryna (Alfred Nobel University Publisher, 2024)
The trend of student-centred education in higher education institutions imposes new requirements on standards within the achievement of professional competencies. This leads to the popularisation of such a technology as learning autonomy, which requires analysis from the perspective of its application in the educational space of higher education institutions. The relevance of this research is determined by the necessity to develop skills in future Doctors of Philosophy (PhD candidates) to independently plan their learning and research activities within the conditions of postgraduate studies. The resolution of this task is based on the skills of implementing goal-setting, project planning, and reflection strategies. On the basis of current educational trends, it becomes possible to analyse learning autonomy as an effective way of teaching future PhD candidates to ensure the successful implementation of their future professional and research activities. The purpose of this research is to examine the concept of "learning autonomy" as an effective method of increasing the awareness of future PhD candidates in the process of developing research competence in terms of postgraduate studies. To achieve this goal, the following tasks were formulated: to consider learning autonomy as an effective method of teaching and personal development of future PhD candidates; to analyse the scientific literature on the stated issue and draw parallels between the definitions of "autonomous learning" and "independent work"; to identify the main advantages of learning autonomy in the context of developing research competence. To achieve the aforementioned tasks, the following theoretical research methods were applied: the method of deduction, content analysis, formalisation, method of generalisation, and systematisation of the results of the existing studies on the stated issue. Study results. The results of the study revealed that the concept of "learning autonomy" is relevant in the context of modern education. Noting the absence of a unanimously accepted definition of this term in pedagogy, the article examines various interpretations proposed by both foreign and domestic researchers. On the basis of the conducted analysis of definitions, the article incorporates our own understanding of the concept of "learning autonomy", emphasising its special importance for future PhD candidates within the conditions of postgraduate studies for the successful and effective development of research competence. The article characterises the main descriptors that comprise learning autonomy, namely: the ability to set goals, target-oriented execution skills, the ability to self-reflect, intellectual independence, interaction and cooperation, self-governance skills, conscious, and effective independent management of learning activities. Relying on practical experience, methods for enhancing learning autonomy have been identified including problem-based teaching, and partially search, research and project methods. The leading strategies of autonomous learning activities for future PhD candidates were identified as follows: primary and auxiliary ones. The primary strategies include learning material acquisition strategies, educational-informational, cognitive, compensatory, creative, and specialised strategies. Auxiliary strategies encompass metacognitive and socio-emotional strategies. It has been concluded that the development of such personal qualities as independence and autonomy is a necessary condition for carrying out independent activities, ensuring the success and continuity of the process of professional development of future specialists within the conditions of postgraduate studies, and the development of their research competence